Discovery of a New Inhibitor of P53/MDM2 Interaction Using a Yeast Target-based Screening Strategy - Lucilia Saraiva (2012)
The p53 tumour suppressor is a major regulator of cell proliferation and death.In tumours that retain a wild-type (wt) p53, the activity of this protein can beinhibited by the endogenous negative regulator MDM2. In this case, inhibitorsof p53/MDM2 interaction have been considered promising drugs for cancertherapy [1,2].In this work, yeast assays consisting of Saccharomyces cerevisiae cellsco-expressing human wt p53 and MDM2 were used for the screening ofinhibitors of p53/MDM2 interaction. In our experimental approaches in yeast,inhibitors of p53/MDM2 interaction, such as Nutlin-3A, revert the inhibitoryeffect of MDM2 on p53-induced growth inhibition/cell cycle arrest as well ason p53-dependent transcriptional activity of a reporter gene (described in [3]).A chemical library of small-molecules inhibitors of tumour cell growth wastested and the small-molecule LEM1 was identified as inhibitor of p53/MDM2interaction. The validation of the molecular mechanism of action of LEM1was carried out in two human tumour cell lines derived from breast cancer(MCF7) and colon carcinoma (HCT116 p53+/+) by performing gene reporterassays and by analysis of p53, p21 and Bax protein levels as well as caspaseactivation by Western blot. The results obtained confirmed that 10 mM LEM1treatment stimulated p53-dependent transcriptional activity, led to p53 proteinstabilization, increased p21 and Bax protein levels, and induced caspase-7activation in human tumour cell lines. Notably, these effects were not observedin the HCT116 p53−/− derivative cell line.In conclusion, an efficient yeast-based high-throughput screening strategy wasestablished to search for inhibitors of p53/MDM2 interaction. Most importantly,with this approach, LEM1 was discovered as an inhibitor of p53/MDM2interaction. LEM1 represents a promising small-molecule to be further exploredas anticancer drug and/or as a lead compound toward the synthesis of morepotent and selective inhibitors of p53/MDM2 interaction.